Quantification of Soluble or Insoluble Fractions of Leishmania Parasite Proteins in Microvolume Applications: A Simplification to Standard Lowry Assay - Bhagya Deepachandi; Sudath Weerasinghe; Thisira Priyantha Andrahennadi; Nadira D. Karunaweera; Nadeeja Wickramarachchi; Preethi Soysa; Yamuna Siriwardana (International Journal of Analytical Chemistry, 2020)
Protein quantification is often an essential step in any research field that involves proteins. Although the standard Lowry assay and its modifications are most abundantly used in protein quantification, the existing methods are rigid or often demonstrate nonlinearity between protein concentration and color intensity. A method for fast and accurate qualitative and/or quantitative determination of total soluble/insoluble proteins or micro-well plate immobilized proteins isolated from Leishmania parasites in microvolumes was described in the current study. Improvements in cost-effective techniques are necessary to increase the research outputs in resource-limited settings. This method is a modification to the established Lowry assay for protein quantification. Concentrations of unknown samples were calculated using a standard curve prepared using a standard series of bovine serum albumin (BSA). The optimized reagents were 2 N NaOH (sodium hydroxide), 2% Na2CO3 (sodium carbonate), 1% CuSO4 (copper sulfate), 2% KNaC4H4O6 (potassium sodium tartrate), and 2 N Folin and Ciocalteu’s phenol. This modified protein assay was sensitive for quantifying Leishmania proteins in a total crude extract or in a soluble fraction within the approximate range of 10–500 μg/ml (1–50 μg/assay) and showed a linearity between color intensity and concentration of the protein. This is an easier, fast, and accurate method for quantifying proteins with microvolumes in a cost-effective manner for routine use in research laboratories in resource-limited settings.